NI-23 ULTRA-HIGH-RESOLUTION CT ANGIOGRAPHY FOR BRAIN TUMOR SURGERY. (16th December 2019) - Saito, Kuniaki; Kobayashi, Keiichi; Iijima, Shohei; Matsumoto, Yoshie; Shimada, Daisuke; Koyanagi, Masamichi; Gomyo, Miho; Shiokawa, Yoshiaki; Nagane, Motoo
Abstract: BACKGROUND: Preoperative accurate evaluation of arteries and veins can help avoid ischemic complication of brain tumor surgery. The latest ultra-high-resolution CT (UHRCT) angiography (Aquilion Precision TM ; Canon Medical Systems) has recently become available for clinical testing of the main arteries and critical perforating arteries by brain CTA, compared to conventional CT. METHODS: UHRCT provides slice collimation of 0.25 mm x 160 and matrix size of 1024 x 1024 or 2048 x 2048. Major features of this CT scanner include an improved detector system (the minimal slice thickness, 0.25 mm; the maximal channel number, 1792) and a small x-ray focus (the smallest size, 0.4 x 0.5 mm) compared to a standard multi-detector CT (MDCT) scanner (the minimal slice thickness, 0.5 mm; the maximal channel number, 896; the smallest x-ray focus size, 0.8 x 0.9 mm). RESULTS: Until July 2019, 168 patients with brain tumor underwent UHRCT angiography. As high resolution image could visualize cortical arteries and cortical veins clearly, it helped to decide approach route to the tumor and achieve accurate biopsy of even small lesion. Identification of tumor feeders and passing arteries allowed for efficient feeder coagulation and preservation of passing artery, avoiding the ischemic change of surrounding brain. Improved image reconstruction could visualize perforating arteries, which helped to preserve perforator by predicting the location during tumor removal. CONCLUSION: UHRCT angiography can visualize even tiny arteries and veins around the tumor, and contributes to avoid the risk of ischemic complication.